The role of state ownership and institutions in the innovation performance of emerging market enterprises: evidence from China - Yi, Jingtao; Hong, Junjie; Hsu, Wen chung; Wang, Chengqi (Elservier, 2017)
Although it has been suggested that institutional context influences a firm's innovation performance, the role of regulatory institutions has been underexplored. Extending previous research, this study investigates whether and how regulatory institutions (i.e. state ownership, region-specific marketization and industry-specific institutional policy) affect innovation performance of emerging market enterprises (EMEs). Evidence derived from a large sample of Chinese manufacturing firms demonstrates that state ownership positively moderates the effect of R&D intensity on innovation performance. However, state ownership is not equally beneficial for all firms. Our analysis shows that region-specific marketization and industry-specific institutional policy enhance the innovation-enhancing effect of state ownership. By revealing the role of regulatory institutions, our study points to the importance of looking beyond firm boundaries to understand why EMEs are able to innovate despite their weak internal capabilities.